EVALUATION OF THE EFFECTIVENESS OF DIGITAL COMMUNICATION STRATEGIES IN CHEMICAL INDUSTRY ENTERPRISES BASED ON KPI AND ROI INDICATORS (Marketing Journal, 2025)
The effectiveness of digital communication strategies in chemical industry enterprises was evaluated based on KPI and ROI indicators. The application of metrics was analyzed using both statistical and qualitative approaches. The impact of various digital c hannels on performance was examined. The relationship between KPI and ROI was assessed as a key tool for strategy improvement. The importance of technological integration in decision -making was identified. Existing systems were shown to play a significant role in enhancing overall effectiveness.
Keywords: KPI; ROI; digital marketing; strategic evaluation; effectiveness; technological integration; chemical industry